An Analysis on The Creation of Condusive Working Envi-ronment Conditions at Bob PT Bumi Siak Pusako-Pertamina Hulu - Siska Sri Wahyuni (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2021)
This research aimed to know the corporation policies, physical and non-physical work environment factors, obstacles and solutions which was faced and carried out made in the creation of a conducive working environment at BOB PT Bumi Siak Pusako-Pertamina Hulu. This research was held at the BOB PT Bumi Siak Pusako-Pertamina Hulu, Zamrud on September 2019. The results of this research indicate that in creating a conducive working environment the corporation makes policies such as the corporation's policy on occupational safety and health, make policies for employees enters at 07.00 until 05.00 pm and enters 10 on/off days, provide counselling related to work environment issues, adherence to the Corporation Regulations, and adherence to the work standards that had been outlined in the SOP.  Cleanliness, room area and lighting, room temperature, health facilities, sports, worship facilities, and libraries were included in discussions of physical work environment factors, moreover, about non-physical environment factors such as relationship of superiors with subordinates and relationships between employees.  There are obstacles like job exchanges that must be explained in detail, workers from outside the area so they do not have to travel from home to work, government regulations that alter profit every day.  To resolve the issue, we arranged to meet more frequently, tried to rest at the guesthouse, and complied with government regulations.